Comparative evaluation of shear bond strength of three pit and fissure sealants using conventional etch or self-etching primer - J K Dhillon; A Pathak (Wolters Kluwer Medknow Publications, 2012)
Aims: To compare the shear bond strength of three different pit and fissure sealants and evaluate the effect of a self-etching primer on shear bond strength of these three pit and fissure sealants as compared to conventional etch. Materials and Methods: One hundred and eighty newly extracted non carious permanent molars were selected. The mesial or distal surface was cleaned and polished to obtain a flat enamel surface. The specimens were randomly divided into three groups of sixty teeth each and each group further divided into two subgroups of thirty each. The teeth in one subgroup were treated with 37% phosphoric acid etchant and the other subgroup with self-etching primer before formation of a sealant button using a Teflon mold. Then specimens were tested in a shear mode at a crosshead speed of 1 mm/minute. Results: The average bond strengths using conventional etch were: (1) Eco-S = 13.0986 MPa; (2) ClinPro = 13.4317 MPa; and (3) Dyract Flow = 13.0292 MPa and with self - etching primer were: (1) Eco-S = 19.7011MPa; (2) ClinPro = 20.8069 MPa; and (3) Dyract Flow = 19.5207 MPa. The values with self-etching primer were higher than and statistically different from those with the conventional etch system (student t test, P < 0.005). Conclusion: It was concluded that the bond strengths of self - etching primer in conjunction with pit and fissure sealant, exceeded those of conventional etch.